The haematological, biochemical and immunological profile of athletes suffering from the overtraining syndrome - Rowbottom, D. G.; Keast, D.; Goodman, C.; Morton, A. R. (European Journal of Applied Physiology, 1995)
Athletes (N = 10) suffering from overtraining syndrome were evaluated for blood parameters. It was found that the debilitating fatigue experienced by overtrained athletes was not related to any blood parameters traditionally associated with chronic exercise stress (levels were normal). The only parameter which deviated significantly from the normal range for the athletes was plasma concentration of glutamine. However, it remains to be shown that there is any correlation between glutamine concentrations and other clinical symptoms of overtraining such as depressed physical capability. Implication: Blood analyses of fatigued athletes are not likely to yield reliable and valid information associated with overtraining.